Szadkowianie zamordowani w Katyniu - Stulczewski, Jarosław (Biuletyn Szadkowski, 2011)
Nearly 15 thousand Polish prisoners-of-war were concentrated by Soviets in three main camps in Kozielsk, Starobielsk and Ostaszków. Among their number were about 300 persons connected with Sieradz region through place of service, birth or residence. By decision of the Political Bureau of the USSR of 5 March 1940, NKWD functionaries killed no less than 21 768 Polish citiens. Victims of this crime were buried in collective graves in Katyn near Smolensk, Miednoje near Twer, or Piatichatki in the suburb of Charkov. Five of the victims are linked to Szadek (three through place of birth and two through place of residence and work): Wojciech Patora, Władysław Franciszek Piekielny, Piotr Werecki, Stanisław Ludwisiak and Jan Lizjusz. The text includes their short profiles.